It takes two to tango: a new partner in amylose synthesis. - Caitlin Sedwick (PLoS Biology)
The mechanism by which plants make starch-a vital foodstuff for billions of humans-is poorly understood, with a clear role for just one enzyme, granular binding starch synthase. A new study identifies a protein needed to recruit this enzyme to the starch granule. Read the Research Article.